Performing Female Blackness - Keleta-Mae, Naila (Book collections on Project MUSE., 2023)
"Performing Female Blackness examines race, gender, and nation in Black life using critical race, feminist and performance studies methodologies. This book examines what private and public performances of female blackness reveal about race, gender, and nation and considers how Canada shapes these performances. Naila Keleta-Mae proposes that performance is part of the ontology of female blackness in the public and private spaces that constitute everyday life because people who are female and Black are constantly expected to perform fantasies-be it their own or, far more commonly, those insisted on by dominant culture. By exploring Black expressive culture in familial, literary, and performance settings, the author demonstrates how people who are read as female and Black in private and public settings, are figuratively on stage regardless of the cultural, political, or historical contexts in which they find themselves. Written in poetry, prose and journal-form and drawing from the author's own life and artistic works, Performing Female Blackness is ideal for scholars, educators, and students of race, gender, performance, and Black expressive culture."--